Execution of Judgments and Advisory Opinions of the Court of the Eurasian Economic Union - P. P. Myslivskiy (Московский журнал международного права)
INTRODUCTION. Since January 1, 2015, a new body of international justice, the Court of the Eurasian Economic Union (hereinafter – Court of the EAEU, the Court) has been functioning. This Court operates in accordance with the Treaty on the Eurasian Economic Union of May 29, 2014 (hereinafter – the Treaty on the EAEU), as well as the Statute of the Court of the Eurasian Economic Union (Appendix No. 2 to the Treaty on the EAEU; hereinafter the Statute). The EAEU Court replaced the Eurasian Economic Community Court (hereinafter – the EurAsEC Court), which functioned from January 1, 2012 to December 31, 2014 and had a scope of powers comparable to the current EAEU Court. These bodies have developed a significant amount of case-law on various issues of Eurasian integration, which, by virtue of paragraph 1 of Article 1 of the Treaty on the EAEU, presupposes freedom of movement of goods, capital, services, and labor forces. Thus, the EurAsEC Court and the EEU Court have delivered judicial acts on various issues of lifting barriers in the Eurasian market, customs classification, regulation of the activities of leasing companies, competition law, the status of foreign athletes in sports competitions, currency movement between the EAEU member states and other issues inwhich international law (EAEU law) was applied and interpreted.MATERIALS AND METHODS. The article examines law on the activities and competence of the EAEU Court, as well as the judicial practice of the EAEU Court and the EurAsEC Court. The article examines the differences between the judicial acts of the EAEU Court – judgments and advisory opinions. The doctrine is considered, which indicates that the decisions of this supranational judicial body (that is, the body to which the Union member states have transferred competence to consider disputes previously considered in national courts in relation to decisions (actions, inaction) of state bodies; access to which is without exhausting domestic legal remedies) entail legal consequences towards an indefinite set of persons (erga omnes), and non-binding acts of the Court, advisory opinions. The practice of execution of decisions and advisory opinions of the EAEU Court at various levels is considered in the present article.During the research, general scientific methods were used: historical, formal legal, system analysis, comparative analysis, etc.RESEARCH RESULTS. The study made it possible to come to the conclusion that by now, in general, a positive practice of execution of decisions and advisory opinions of the EAEU Court has been formed. This body influences the legal reality of both the EAEU and its member states through the judicial acts rendered by it – the EAEU Court makes decisions that are generally executed by the EAEU member states, the EEC voluntarily or compulsorily. At the same time, the EAEU court does not always take into account its own practice in the cases under consideration. The advisory opinions of the EAEU Court are сonsidered by both the EEC and the member states of the Union in the context of lawmaking and law enforcement.DISCUSSION AND CONCLUSIONS. The topic of the article aims to reveal how the decisions and advisory opinions of the EAEU Court are executed. The study identified the features of the competence of the EAEU Court at the present stage, as well as possible ways of its development until 2025. The similarities and differences of judicial acts of the EAEU Court – binding decisions and non-binding advisory opinions – are considered. It was concluded that the decisions of the EAEU Court differ from decisions of other international courts – they are binding erga omnes and have the functions of restoring violated rights and directing the judicial practice of national courts, while the advisory opinions can be considered exclusively non-binding only in part, since they contribute to the formation of opinio juris of States and the Eurasian Economic Commission.The study showed that the execution of decisions and advisory opinions of the EAEU Court occurs at various levels – by the Court itself, by the losing party (voluntarily or compulsorily), in the national judicial authorities; the practice of execution of advisory opinions made it possible to reveal that the advisory opinions of the EAEU Court are essential, since they form opinio juris in the EAEU and are taken into account by national judicial and legislative bodies in various fi lds – antitrust regulation, establishing the status of foreign players in sports competitions and others, as well as helping to protect the interests of international civil servants of the EAEU bodies.